Avaliação da qualidade do ambulatório de pessário vaginal para tratamento conservador do prolapso de órgãos pélvicos - Gomes, Maria Laura Silva (2019)
The vaginal pessary is a device used as the first conservative treatment line for pelvic organ prolapse in international consensus. It is as effective as surgery, with less risk of complications and few contraindications. In Fortaleza, only in 2013 did it become part of the therapeutic arsenal for prolapse in a reference Urogynecology service in the state of Ceará and, since then, this service has never undergone an evaluation of its effectiveness. Thus, the objective was to evaluate the quality of the conservative treatment service of the prolapse using the pessary. This is an evaluative study developed from June to November 2019, considering the three main elements for health evaluation processes defended by Avedis Donabedian - structure, process and results. For the first, the information was obtained through site visits. In relation to the process and result, through the consultation of the medical record and application of instruments to evaluate the users' satisfaction. The instruments were constructed and adapted from other evaluative studies and criteria adopted by the national health management. For the evaluation of satisfaction, Service Performance (SERVPEF) was also used, composed of 22 items distributed in five domains, and national instruments for assessing the quality of services. Data were analyzed using the Statistical Package for Social Sciences Program (SPSS) version 22.0, using the Mann-Whitney Test for interval variables, the Chi-Square Test for dichotomous variables and the Likelihood Ratio for women. categorical variables. It was identified that the service has a structure in accordance with that recommended in the analyzed literature. Regarding the aspects related to the process and result, the following percentages of 170 participants were obtained: 100% acceptance, 72.9% successful insertion and 56.5% continued use, with average use time, among women who remain with the device for 27.5 ± 20.0 months; and, in the dropout group, 11.4 ± 14.7 months. Women with body mass index ≥30 (OR: 4.74; 1.98 - 11.32) and sexually active women (OR: 2.26; 1.47-4.91) are more likely to experience failure to insert of the vaginal pessary. For the assessment of user satisfaction, 74 women participated in the study, who underwent testing the pessary for conservative POP therapy. It was found that women generally wait from 61 to 90 days to make the first appointment at the service, they wait up to 2 hours to be seen, they feel safe with the interaction with health professionals; and report that they received quality information about the risks and benefits at the time of decision making. Still, the respondents pointed out that the professionals confirm the name before starting the consultation, clean their hands before and after the procedures and take measures to prevent falls. Most of the areas for assessing satisfaction with SERVPERF had a high level of quality. Among the points that need to be reassessed by the service, are related to the need to expand the hours of service and reduce the waiting time for care. Despite being only six years old, the Pessary Ambulatory offers a quality service with an adequate structure, effectiveness of the actions offered and user satisfaction.